Formation of Structural-Phase State in a Cobalt-Chromium-Molybdenum Alloy by Selective Laser Melting; Solid State Phenomena; Vol. 313 - Saprykin A. A. Aleksandr Aleksandrovich; Sharkeev Yu. P. Yury Petrovich; Saprykina N. A. Natalia Anatolyevna; Khimich M. A. Margarita Andreevna; Ibragimov E. A. Egor Arturovich (2021, 2021)
Title screen